Meaning of bleeding follicles chorionic gonadotropin therapy - San Martín, M. (2015)
The results show that it is necessary a balance between the PMSG and the CG to obtain ovulation of the induced mature follicles. The hemorragie follicles without ovulation could he produced by insufficient amounts of CG in relation to the PMSG used to induce the follicular maturation.